Tracing the Labor Absorption Rate in the Medium and Large Industrial Sectors - Sitti Aisyah; Sulastri Sulastri (EcceS (Economics, Social, and Development Studies), 2020)
The high rate of population growth and the workforce raises the problem of job opportunities, because it involves various aspects both economic and non-economic. At the same time as massive industrialization, it is not automatically able to create adequate work. This study aims to analyze and determine the effect of the number of business units, the provincial minimum wage, and economic growth on the rate of labor absorption in the medium and large industrial sectors in South Sulawesi in the period 2010-2019. This research is expected to be one of the benchmarks for the government and private sector in paying attention to the absorption rate of labor in the industrial sector in South Sulawesi. The type of research used in this research is quantitative. The type of data used in this study is secondary data. The data used in this study are time series data in the years 2010-2019. The results of this study indicate that (1) the number of business units has a positive and significant effect on the rate of employment in the industrial sector in the province of South Sulawesi, (2) the provincial minimum wage has a negative and significant effect on the rate of employment in the medium and large industrial sector in South Sulawesi, (3) economic growth has a significant effect in a negative direction on employment in the medium and large industrial sectors in South Sulawesi. The government should design an industrialization policy direction that should be more inclusive, the incoming investment should be based on empowering local workers, reducing unemployment, creating more expansive employment opportunities and synergizing local economic development.Keywords: Economic Growth; Industry; Labor; Wages.